Nota técnica: Series de ahorro e ingreso por agente económico en Chile, 1960 - 1997 - Bennett, Herman; Schmidt-Hebbel, Klaus; Soto, Claudio (Estudios de Economía, 2016)
This paper presents new sector saving series for Chile. The annual series for 1960-1997 are disaggregated by six sectors: external sector, general government, public enterprises, central banks, private firms, and households. Household saving is disaggregated into mandatory pension saving and voluntary saving. The series reported here were constructed to ensure consistency in the face of limitations of the data available from different sources. Various features distinguish the saving series reported here from those available before. Capital depreciation is disaggregated by sector to avoid the bias implicit in assigning aggregate depreciation to private firms only. Better estimations of mandatory pension saving of households are provided. Alternative sector saving series adjusted for capital gains and losses due to domestic inflation and exchangerate depreciation are reported. Finally sector income series are presented by combining the saving series with consumption series from national accounts.